Novel Composite Polymer Electrolyte Membranes Based on Poly(vinyl phosphonic acid) and Poly (5-(methacrylamido)tetrazole) - Sinirlioglu, Deniz; Celik, Sevim Unugur; Muftuoglu, Ali Ekrem; Bozkurt, Ayhan (WILEY, 2015)
Heterocyclic molecules are generally used in the proton conducting membranes as dopant or polymer side group due to their high proton transfer ability. Composite proton conducting membranes based on poly(vinylphosphonic acid) (PVPA) and poly(5-(methacrylamido)tetrazole) (PMTet) were produced. The homopolymers, prepared from their corresponding monomers, were blended at several mol ratios to obtain the polymer electrolyte membranes. All samples were characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), thermogravimetric analysis (TGA), differantial scanning calorimetry (DSC), cyclic voltammetry (CV), and impedance analysis. Besides, the morphology of the membranes was studied by X-ray diffraction (XRD), atomic force microscopy (AFM) and scanning electron microscopy (SEM). FTIR spectra confirmed the formation of hydrogen bonding network between PVPA and PMTet units. TGA showed that the polymer electrolyte membranes were thermally stable up to approximate to 210 degrees C. CV curves demonstrated the oxidative stability of the samples in 3 V region. In anhydrous conditions, the maximum proton conductivity was determined as 0.06 Scm(-1) at 150 degrees C for PMTetP(VPA)(4). POLYM. ENG. SCI., 55:260-269, 2015. (c) 2014 Society of Plastics Engineers
Keywords: ANHYDROUS PROTON CONDUCTIVITY; VINYLPHOSPHONIC ACID; BLEND MEMBRANES; TRIAZOLE; COPOLYMERS; POLY(1-VINYL-1,2,4-TRIAZOLE); TETRAZOLE; Engineering; Polymer Science